Pelatihan Dan Pendampingan Kader Kesehatan Gigi Pada Guru SD Manefu Kecamatan Taebenu - Merniwati Sherly Eluama; Mery Novaria Pay; Leny M.A Pinat; Applonia Leu Obi; Christina Ngadilah; Melkisedek O. Nubatonis (CV. Ulil Albab Corp, 2022)
Proper care for dental and oral health needs to be performed since early ages. Elementary school students should develop good habit related to dental health by regular teeth brushing and consuming health food, including at school. Dental health cadres have been appointed to assist dental health workers in carrying out efforts to maintain the dental and oral health of school members. Teachers are potential dental health cadres who can guide students to develop proper dental health behavior at schools. Purpose: This community service was administered to enhance the knowledge and skills of dentalhealth cadres to be able to assist elementary school students in improving their dental and oral health. Method: The training was conducted through lectures, demonstrations and simulations for teachers as dental health cadres at Manefu Elementary School, Taebenu District. Some educational media were used including posters, phantoms and toothbrushes and training manuals. Training and simulations on how to properly brush teeth and maintain dental health were held. In this study,a quasi-experimental pretest and posttest design was also performed and data of the study were analyzed using the paired sample test. Results: Training and assistance program for dental health cadres was found effective in improving the knowledge and skills of dental health cadres with a p-value of 0.000.